Ética na pesquisa em Administração - Leite, Ana Patrícia Rodrigues (2012)
Ethics on scientific research is approached and often discussed in several areas of knowledge connected to health. In the Administration area there are very few studies which approach the topic of ethics on research. The present paper tried to fill in this gap in the production of knowledge about the topic, investigating how the ethical principles found in the literature and in the codes of conduct are noticed and taken into account in Administration research activities developed by acting researchers in Administration Post Graduation Programs. Theoretically speaking, the study was based mainly on the approaches by Creswell (2007) and Bell and Bryman (2007), which discuss the research ethical principles. Methodologically speaking it was all about an exploratory kind of study, with qualitative research approach. Upon data collection, personal interviews were made aiming at its depth and focus groups were formed. The first stage had interviews with four experienced researchers who took part on a teaching and researching event and on the second stage we used the focus group technique. The focus groups were done in four college institutions along with the post graduation programs in Administration in the states of Rio Grande do Norte, Paraíba and Pernambuco, in Brazil. The results suggest the existence of general principles and parameters for the scientific research recommended in the literature and on official resolution. However, in the Administration area, there are only a few recommendations of good practices when it comes to submitting articles for scientific publications but we found no guidance with ethical principles and parameters which cover all the activities in the scientific research and which specifically meet the research particularities in Administration. The main ethical dilemma pointed by the researchers refers to ethical questions which arise at the time of data collection and on disclosing the results. Most researchers do not know the guidelines and the ethical norms on ethics about research that we have in our country neither do they send in their projects to the research ethics committee. When dilemma arises, they decide the ethical question based on their values and common sense. These elements confirm the thesis that the researcher s procedure in the research activities in Administration is predominantly signed by personal values or by common sense and less by ethical principles, whether by not knowing the normative instruments related to ethics or by disagreeing with any disciplining rules on ethical behavior in the research